Exploring Niches for Short-Season Grain Legumes in Semi-Arid Eastern Kenya — Coping with the Impacts of Climate Variability - Sennhenn, Anne; Njarui, Donald M. G.; Maass, Brigitte L.; Whitbread, Anthony M. (Frontiers in Plant Science, 2017)
Climate variability is the major risk to agricultural production in semi-arid agroecosystems. Short-season grain legumes have great potential to address this challenge and help to design more resilient and productive farming systems. Three contrasting short season grain legumes (common bean (Phaseolus vulgaris L.), cowpea (Vigna unguiculata (L.) Walp.) and lablab (Lablab purpureus (L.) Sweet) were selected to better assess their agricultural potential with respect to climate variability and change along the Machakos-Makueni transect in semi-arid Eastern Kenya using measured data (water response trial, 2012/13 and 2013/14 in Machakos, Kenya) and simulated data (using Agricultural Production System sIMulator (APSIM). The APSIM crop model was calibrated and validated to better simulate growth and development of short-season grain legumes in semi-arid environments. Water use efficiency (WUE) was used as indicator to quantify the production potential. The major traits of adaptation include early flowering and pod and seed set before the onset of terminal drought. Early phenology together with adapted canopy architecture allowed more optimal water use and greater partitioning of dry matter into seed. While common bean followed a comparatively conservative strategy of minimizing water loss through crop transpiration, the very short development time and compact growth habit limited grain yield to rarely exceed 1000 kg ha-1. An advantage of this strategy was relatively stable yields independent of in-crop rainfall or season length. The growth habit of cowpea in contrast minimized water loss through soil evaporation with rapid ground cover and dry matter production, reaching very high grain yields at high potential sites (3000 kg ha-1) but being highly susceptible to in-season drought. Lablab seemed to be best adapted to dry environments as its canopy architecture appeared to be a good compromise between the right investment in biomass as a prerequisite to accumulate grain yield by minimizing water loss through soil evaporation and crop transpiration at the same time, reaching grain yields of up to 2000 kg ha-1 at high potential sites and >1000 kg ha-1 at low potential sites. The climate-smart site-specific utilization of the three legumes offers promising options to design more resilient and productive farming systems in semi-arid Eastern Kenya.